Changes of Muscle Insulin-like Growth Factor-I and Concentrations of Inflammatory Cytokines in Rat Skeletal Muscle Following Denervation and Diabetes-induced Atrophy - 김영식; 박은기; 안예찬; 박충무; 전병환 (The Asian journal of kinesiology, 2016)
[PURPOSE] Muscle atrophy is the result of several diseases and conditions. In systemic disease, many factors contribute to muscle atrophy. Insulin-like growth factor-I (IGF-I) is a local and systemic hormone that contributes to muscle growth. The aim of this study was to investigate the changes in muscle protein synthesis biomarkers and pro-inflammatory factors associated with muscle atrophy in systemic disease. [METHODS] Local muscle tissue damage was observed and compared in both streptozotocin (STZ) -induced diabetic and denervated rats. In these animal models, we measured the expression of muscle-specific IGF-1 (mIGF-1) in by real-time PCR and serum concentrations of inflammatory cytokines by ELISA. In addition, muscle mass and blood glucose levels were observed for six weeks. [RESULTS] The results showed that muscle mass was significantly lower in both experimental groups compared to the control group from week two. Over the six week period, muscle mass gradually increased in the control group, dramatically decreased in the denervated group, but interestingly, showed no significant changes in the diabetes group. Inflammatory factors including tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were significantly higher in diabetic rats than in the control group. The level of TNF-α was increased at week four; however, IL-6 levels did not change in denervated rats. The expression of mIGF-1 mRNA did not change significantly in the two experimental groups. [CONCLUSIONS] In conclusion, mIGF-1 for the proliferation of muscle cells did not have an effect on muscle atrophy among the groups. However the increase in systemic inflammatory factors may be involved in the process of muscle atrophy in diabetic rats. KCI Citation Count: 0